DEVELOPMENT OF STUDENTS' MENTAL ACTIVITY THROUGH INFORMAL COMMUNICATION (TAMADDUN NURI JURNALI, 2024)
This article is devoted to analyzing the influence of non-verbal communication on students' mental activity. The importance of non-verbal communication in developing students‘ communication skills is analysed, which effectively influences students’ concentration, creative thinking, empathy and communication through body language, facial expressions, hand movements and other non-verbal means. Analyses ways of developing mental skills such as participation and illustrates examples of how non-verbal communication helps students express their feelings, thoughts and concerns.